Preliminary Analysis of Modified Low-Density Lipoproteins in the Serum of Healthy and Obese Dogs and Cats - Mori, Nobuko; Okada, Yuki; Tsuchida, Naoto; Hatano, Yutaka; Habara, Makoto; Ishikawa, Shingo; Yamamoto, Ichiro; Arai, Toshiro (Frontiers in Veterinary Science, 2015)
Oxidized low-density lipoprotein (LDL) is thought to play an important role in the inflammatory response associated with human obesity. The purpose of this preliminary study was to determine oxidized LDL concentrations in healthy dogs and cats, and to evaluate whether obesity affects oxidized LDL concentration, using 39 cats and 19 dogs that had visited 2 different veterinary clinics in Japan. We hypothesized that oxidized LDL concentrations measured against body condition score (BCS) may have a potential value in evaluating the qualities of accumulated or circulating lipids in obese dogs and cats that do not show signs of metabolic diseases. The mean oxidized LDL value in BCS3 dogs (2.4 ± 0.9 μg/dl) was very similar to that of BCS5 dogs (2.2 ± 0.3 μg/dl). The mean oxidized LDL value of BCS4 dogs was 7.2 ± 10.3 μg/dl and the highest among three groups. BCS4 dogs included two dogs whose oxidized LDL values were higher than the mean oxidized LDL value of healthy humans (11.2 ± 0.3 μg/dl). On the other hand, the mean oxidized LDL value of BCS3 cats was 2.5 ± 0.9 μg/dl, and those of BCS4 and 5 cats were higher than that of BCS3, but there was no significant difference. The BCS4 cat group included one cat with a higher oxidized LDL value, and the BCS5 group also included two cats with oxidized LDL values higher than the mean oxidized LDL value of healthy humans. Interestingly, the oxidized LDL values in 2 obese dogs and 3 obese cats were indeed higher than the mean oxidized LDL value of humans with coronary artery disease (20.1 ± 1.1 μg/dl). In conclusion, this preliminary study showed reference ranges of oxidized dogs and cats against BCS. Obesity alone does not appear to have any direct effect on serum oxidized LDL values in healthy dogs and cats.